Perspectives on Sino-Japanese diplomatic relations - Rossman, John; Yomiuri Shinbunsha. Seijibu (Tokyo : Japan Publishing Industry Foundation for Culture (JPIC), 2017)
"In East Asia, the growth center of the post-Cold War world, two reg ional powerhouses survey one another from opposite sides of the Japan S ea. China, a rising power with tremendous economic clout and an increas ingly assertive foreign and military policy, and Japan, a respected lea der in the region and a mature nation enjoying its greatest political s tability in many years, must coexist for the peace and prosperity of Ea st Asia and the Asia-Pacific. but just how well can these neighbors - a nd oftentimes rivals - get along? What stands in the way? And who else is caught up in their volatile relationship?"--Back cover.
Cold war between Japan and China -- Senkaku turbulence -- Japan-U.S. alliance and Okinawa -- Hidden war -- Cooperation by Japan, the U.S., Australia, and ASEAN encircling China -- The ruthless economic battle b etween Japan and America's TPP and China's AIIB -- China needs to learn from Showa history -- Chronology of key events.
"This book is an English version that compiles sections from three J apanese publications. Sections 1 to 4: Sections 1, 2, 4, and 5 of Nitch ukan gaiko senso by Shinchosha, 2014. Sections 5 and 6: Sections 2 and 3 of Abe kantei vs. Shu Kinpei by Shinchosha, 2015. Section 7: Section 4 of Ryodo soshitsu no akumu by Shichosha, 2014. Chronology of Key even ts: Excerpt from the chronologies of Nitchukan gaiko senso by Shinchosh a, 2014 and Abe kantei vs. Shu Kinpei by Shinchosha, 2015"--Title pages verso.
In English, translated from the original Japanese.
Keywords: Japan -- Foreign relations -- China; China -- Foreign relations -- Japan